2002
DOI: 10.1086/324540
|View full text |Cite
|
Sign up to set email alerts
|

Feii/MgiiEmission‐Line Ratios of QSOs within 0 <z< 5.3

Abstract: Near-infrared spectra of 13 QSOs located between 4.4 \ z \ 5.3 were obtained by the OH-airglow suppression spectrograph mounted on the Subaru telescope. The Fe II/Mg II emission-line ratios of the QSOs at various redshifts were examined by applying the same Ðtting algorithm to the present data together with published or archived spectra. We found a trend of a decreasing Fe II/Mg II ratio from z D 5 to 1.5, almost independent of their luminosities. We also conÐrmed the Baldwin e †ect on the Mg II emission line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 34 publications
(26 reference statements)
11
81
0
Order By: Relevance
“…Kelly et al (2010) and Willott et al (2010b) have shown that the intrinsic Eddington ratio distribution for a volume-limited QSO sample is indeed shifted toward lower values with respect to a luminosity-selected population. Our estimate hence represents an upper limit on the characteristic Eddington ratio of the z ∼ 6 QSO population: lower Eddington (Iwamuro et al 2002); black triangles: literature sample, z ∼ 6 (Barth et al 2003;Iwamuro et al 2004;Jiang et al 2007;Kurk et al 2007Kurk et al , 2009 ratios, according to Equation (9), would yield even longer times for the BH seeds to grow. In the future, with complete samples of QSOs at z ∼ 6, it will be possible to give better constraints on the SMBH formation models.…”
Section: Impact On Bh Formation Historymentioning
confidence: 94%
See 1 more Smart Citation
“…Kelly et al (2010) and Willott et al (2010b) have shown that the intrinsic Eddington ratio distribution for a volume-limited QSO sample is indeed shifted toward lower values with respect to a luminosity-selected population. Our estimate hence represents an upper limit on the characteristic Eddington ratio of the z ∼ 6 QSO population: lower Eddington (Iwamuro et al 2002); black triangles: literature sample, z ∼ 6 (Barth et al 2003;Iwamuro et al 2004;Jiang et al 2007;Kurk et al 2007Kurk et al , 2009 ratios, according to Equation (9), would yield even longer times for the BH seeds to grow. In the future, with complete samples of QSOs at z ∼ 6, it will be possible to give better constraints on the SMBH formation models.…”
Section: Impact On Bh Formation Historymentioning
confidence: 94%
“…Notes. Column 1: QSO name; Columns 2 and 3: QSO right ascension and declination in J2000.0; Column 4: optical redshift from discovery paper; Column 5: NIR spectrum reference paper for the NIR spectra: A, Iwamuro et al (2002); B, Iwamuro et al (2004); C, Barth et al (2003); D, Kurk et al (2007); E, Kurk et al (2009);F, Jiang et al (2007).…”
Section: New Datamentioning
confidence: 99%
“…Of course another way to obtain a featureless continuum is to have metallicities significantly below the solar value used here. This is highly unlikely as quasars are famously known to have enhanced metallicities [53], with a near flat evolution from z = 0 up to z ∼ 4 − 5, after which it is possible that it declines to solar or even subsolar values [54].…”
Section: Individual Image-b Spectramentioning
confidence: 99%
“…Yet no evolutionary effect in the Fe ii (UV)/Mg ii ratio, up to z $ 6:4, has been found (e.g., Iwamuro et al 2002;Barth et al 2003;Diedrich et al 2002Diedrich et al , 2003. The implied abundances and their ratios show large scatter.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made during last several decades to measure Fe ii (UV)/Mg ii ratios in QSOs and connect them with corresponding abundances (e.g., Kwan & Krolik 1981;Iwamuro et al 2002Iwamuro et al , 2003Iwamuro et al , 2004Freudling et al 2003). Two major techniques for subtracting or estimating the Fe ii emission spectra exist.…”
Section: Introductionmentioning
confidence: 99%